Penyalahgunaan Narkotika Sebagai Suatu Tindak Pidana Dalam Tinjauan Kriminilogi Di Wilayah Hukum Polres Bintan - Hutagalung, Evan Ivander; Siahaan, Benny Enrico; Hakim, Aqila Fikril (Universitas Batanghari Jambi, 2023)
Narcotics is like a double-edged knife which can be interpreted that the use of narcotics is good in the field of medicine but wrong when used illegally, causing criminal acts. This research examines the abuse of narcotics in the jurisdiction of Bintan Police based on criminological reviews.Â This research uses empirical research methods or field research with a descriptive qualitative approach. There are 2 problem formulations in this study, namely: What are the factors that cause narcotics abuse in the jurisdiction of Bintan Police Station? and How are efforts to overcome narcotics abuse in the jurisdiction of Bintan Police Station? The conclusion in this research is that weak self-control, low education, work environment and economic problems are the main factors causing narcotics abuse in the jurisdiction of Bintan Police Station. The countermeasures taken by Bintan Police are repressive efforts or prosecution efforts after the occurrence of criminal acts and preventive efforts, namely by conducting socialization, counseling, and establishing cooperation with community leaders, non-governmental organizations, and BNNK.